Consecuencias psicológicas de la pandemia COVID-19: estrés en madres por la educación virtual - Calle Chamorro, Allison Catalina; Quishpi Rueda, Steeven Paul (Machala: Universidad Técnica de Machala, 2022)
The purpose of this research is to analyze the stress in mothers due to the virtual education of their children because of the Covid-19 pandemic. This study is based on the epistemological approach of Positive Psychology, which has stood out from other models for approaching the mental health panorama through the positive vision in the structure of the human being, without leaving aside the crises that are solved by the development and strengthening of internal resources. Three themes of analysis were established, the effects of stress on mothers, the personal resources they possess, and their external coping resources. The sample was composed of five mothers who experienced stress during their children's virtual schooling, residents of the province of El Oro, two of them in the city of Pasaje and three in the canton of Huaquillas, all with children under 12 years of age who attended their education online during the pandemic. The approach of this study is qualitative with a phenomenological-hermeneutic design, with a non-probabilistic-homogeneous sample, and according to the progress of the data collection, the saturation of the categories was reached with five participants. At the beginning of the data collection, the first approach was made with each of the participants, obtaining a favorable response of their participation through informed consent, subsequently, a semi-structured interview was used to collect information based on the interview guide prepared by the researchers, in addition to the Sentence Completion technique that allows exploring the subjectivity of the participants in relation to the phrases proposed, finally, an in-depth open interview was used, in conjunction with qualitative observation to delve into the details and personal characteristics of the participants. According to the rigorous search for theoretical resources, based on both pioneering and current authors, results were obtained that show that the effect of stress on mothers has caused them to develop physical and psychological symptoms and complications in their role as teachers at home, As for personal resources, categories such as resilience, emotional intelligence, attachments, self-efficacy, sense of coherence and hope were identified in the participants, it was also found that factors such as family support and economic solvency alleviated the impact of stress; on the other hand, the use of technologies applied to education has demanded that mothers adapt to these devices, reflecting this as a risk factor for stress. As a conclusion of the study, virtual schooling has been a challenge for mothers who adopted the role of teachers during the pandemic, leading them to experience physical and mental health conditions due to stress, however, having internal resources and protective elements provide containment against stress.
El propósito de esta investigación es analizar el estrés en las madres debido a la educación virtual de sus hijos a causa de la pandemia Covid-19. Este estudio se fundamenta en el enfoque epistemológico de la Psicología Positiva, que se ha destacado de otros modelos por abordar el panorama de la salud mental a través de la visión positiva en la estructura del ser humano, sin dejar de lado las crisis que son resueltas por el desarrollo y fortalecimiento de recursos internos. Se establecieron tres temas de análisis, efectos del estrés en las madres, los recursos personales que poseen, y los recursos externos de afrontamiento de las mismas. La muestra estuvo compuesta por cinco madres de familia que experimentaron estrés durante la escolaridad virtual de sus hijos, residentes en la provincia de El Oro, dos de ellas en la ciudad de Pasaje y tres en el cantón Huaquillas, todas con hijos menores de 12 años que cursaron su educación en línea durante la pandemia. El enfoque de este estudio es cualitativo de diseño fenomenológico- hermenéutico, con una muestra de tipo no probabilístico-homogénea, y acorde al avance de la recolección de datos, se llegó a la saturación de las categorías con cinco participantes. Al inicio de la recolección de datos se tuvo el primer acercamiento con cada una de las participantes, obteniendo una respuesta favorable de su participación a través del consentimiento informado, posteriormente, se utilizó una entrevista semiestructurada que sirvió para recoger información en base a la guía de entrevista elaborada por los investigadores, además de la técnica de Completamiento de Frases que permite explorar la subjetividad de las participantes en relación a las frases planteadas, finalmente, se utilizó una entrevista abierta a profundidad, en conjunto con la observación cualitativa para ahondar en los detalles, y características personales de las participantes. Acorde a la búsqueda rigurosa de recursos teóricos, fundamentada tanto en autores pioneros como en actuales, se obtuvieron resultados que demuestran que el efecto del estrés en las madres de familia ha hecho que desarrollen síntomas físicos, psicológicos y complicaciones en su rol de docentes en casa, en cuanto a los recursos personales, se identificaron categorías como la resiliencia, inteligencia emocional, apegos, autoeficacia, sentido de coherencia y esperanza en las participantes, también se constató que factores como el apoyo familiar y la solvencia económica alivianaron el impacto del estrés, por otro lado, el uso de tecnologías aplicadas a la educación, ha demandado que las madres se acoplen a estos dispositivos, reflejando aquello como un factor de riesgo para el estrés. Como conclusión del estudio, la escolaridad virtual ha sido un reto para las madres de familia que adoptaron el rol de docentes durante la pandemia, llevándolas a experimentar afecciones en su salud física y mental por el estrés, no obstante, contar con recursos internos y elementos protectores proporcionan una contención frente al estrés.
Keywords: MADRE DE FAMILIA; EDUCACION VIRTUAL; RECURSO EXTERNO; RECURSO PERSONAL